Unraveling bisphenol A pharmacokinetics using physiologically based pharmacokinetic modeling - Yang, Xiaoxia; Fisher, Jeffrey W. (Frontiers in Pharmacology, 2015)
Physiologically based pharmacokinetic (PBPK) models integrate both chemical- and system-specific information into a mathematical framework, offering a mechanistic approach to predict the internal dose metrics of a chemical and an ability to perform species and dose extrapolations. Bisphenol A (BPA), because of its ubiquitous presence in a variety of consumer products, has received a considerable amount of attention from the public and regulatory bodies. PBPK models using deuterated BPA were developed for immature and adult rats and non-human primates and for adult humans to understand better the dosimetry of BPA. The focus of the present paper is to provide a rationale for interpreting species- and age-related pharmacokinetics of BPA. Gastrointestinal tract metabolism was an important consideration to predict unconjugated BPA serum kinetic profiles in adult and immature rats and monkeys. Biliary excretion and enterohepatic recirculation of BPA conjugates accounted for the slowed systemic clearance of BPA conjugates in rats. For monkeys, renal reabsorption was proposed as a mechanism influencing systemic clearance of BPA conjugates. The quantitative understanding of the processes driving the pharmacokinetics of BPA across different species and life stages using a computational modeling approach provides more confidence in the interpretation of human biomonitoring data and the extrapolation of experimental animal findings to humans.